Sustainable Tourism Development in Indonesia: Bibliometric Review and Analysis - Megandaru Widhi Kawuryan; Aqil Teguh Fathani; Eko Priyo Purnomo; Lubna Salsabila; Novia Amirah Azmi; Deni Setiawan; Mochammad Iqbal Fadhlurrohman (Indonesian Journal of Geography, 2022)
Along with the many potentials in developing the tourism sector and impressive research in the tourism sector, in the last ten years, interest in studying and researching the sustainability of the development of Indonesia's tourism sector has continued to increase significantly. However, despite the increase, the scientific literature published so far has not evaluated in detail the sustainability of Indonesia's tourism development. This study analyzed 861 articles published until February 2021 in the Scopus database on Indonesia's tourism development sustainability. In conducting the analysis, the VosViewer software was used to find results about the most contributing authors, the number of citations, regions, organization, publica-tions and co-occurrences of keywords that could provide new gaps in future research. The results obtained showed trends and impacts of literature published to date, then new gaps/novelties for further research related to the themes of sport tourism, mangrove tourism, sharia tourism and Indonesia's tourism resilience were found. With these results, the next researchers should raise the theme so that Indonesian tourism's sustainability can develop adequately to have a more significant impact in the future.